A LITERARY REVIEW OF THE MEDIEVAL ARABIC WRITINGS ON KANEM – BORNO - Sirajudeen, Adam Adebayo (Journal of Al-Tamaddun, 2013)
Consequent upon the need of Arab ? Muslim rulers to acquire information such as would assist in handling commercial and political relations with some Islamic empires situated at Africa South of Sahara, Arab geography and history developed in the 7th Century. Arab geographers, travellers, and traders produced a corpus of literary works in Arabic, which later became the primary source of early African historiography. In spite of the tremendous significance of these Arabic writings, to the reconstruction of African history, with particular reference to Kanem Borno, some limitations abound in the works, borne out of technical reasons. This has made the writings to be scarcely considered for historical materials sensu stricto. This paper examines some of the technical problems associated with these literary writings in historiographical perspectives as it relates to Kanem Borno Empire